Prejudice in the wake of terrorism: The role of temporal distance, ideology, and intergroup emotions. (1st March 2018) - Choma, Becky L.; Jagayat, Arvin; Hodson, Gordon; Turner, Rhiannon
Abstract: The shootings at the Canadian Parliament on October 22, 2014 received international coverage and fueled concerns about terrorism and growing Islamoprejudice. In the wake of this event, our two studies ( n  = 215, n  = 492) investigated objective temporal distance, right-wing ideology, and intergroup emotions as predictors of prejudice, outgroup trust, and the restriction of civil liberties. Objective temporal distance from the shootings was also examined as a moderator of the relations between ideology and intergroup emotions with intergroup attitudes. Results showed that greater endorsement of right-wing ideologies, higher intergroup anxiety, or higher intergroup disgust were associated with greater prejudice and lower outgroup trust. Of particular note, participants who completed the survey further from (vs. closer to) the event reported more positive intergroup attitudes and were less likely to endorse restricting civil liberties. Objective temporal distance also moderated some of the associations between intergroup emotions with intergroup attitudes. Implications are discussed. Highlights: Tested temporal distance, ideology and intergroup emotions as predictors of prejudice Two studies were run following the shootings at Canadian Parliament on Oct 22 2014. Being further from (vs. closer to) the event predicted more tolerant attitudes Authoritarian ideology and intergroup emotions predicted greater prejudice. Temporal distance interacted with emotions for some criterion variables.